Matching strategy for patients with platelet transfusion refractoriness caused by compound antibodies against HLA and CD36 - Jing DENG; Xiuzhang XU; Huibin ZHONG; Bi ZHONG; Yangkai CHEN; Jing LIU; Haoqiang DING; Wenjie XIA; Dawei CHEN; Yaori XU; Xin YE (Zhongguo shuxue zazhi, 2023)
Objective To search compatible and suitable platelets for platelet transfusion refractoriness (PTR) patient caused by compound antibodies against HLA and CD36. Methods ELISA method was used to detect the antibody against platelet antigens and the specificity of HLA-I antibody in PTR patients. The specificity of HLA-I antibody and corresponding epitopes of patients were analyzed using MATCH IT! and HLA Matchmaker software. The HLA genotype of both donor and patient was obtained by HLA-SSO method. Compatible or suitable donor platelets for PTR patients were searched through cross-reactive group (CREG) of HLA-I and HLA epitope-matched approach (Eplet). The matching degree was identified using monoclonal antibody-specific immobilization of platelet antigens (MAIPA) and the platelet suspension immunofluores-cence test (PIFT). Finally, the transfusion effect was evaluated according to the corrected count increment (CCI). Results Compound antibodies against both CD36 and HLA-I antigens were detected in two PTR patients, and their phenotype of CD36 was conformed to be type I deficient. Through LSA testing, high-frequency of HLA -I antibodies was found in these two patients, and the panel reactive antibody in patients 1 and 2 was 56% (54/96) and 53% (51/96), respectively. According to HLA-CREG and Eplet matching strategies, one donor of grade C-matching with patient 1 and one donor of grade D-matching with patient 2 were screened from the CD36 deficiency donor bank, respectively. And the selected donors avoided the antigen of HLA-I antibody epitope. These results of MAIPA and PIFT also confirmed that no immune response was detected between the patient and the donor. And a CCI of >4.5 within 24 hour of transfusion of compatible platelets was obtained in patient 2. Conclusion For PTR patients caused by HLA and CD36 compound antibodies, a combination strategy including serological cross-matching, HLA-CREG and Eplet approach should be used to select the CD36 deficient donor platelets which evaded the antigen corresponding to HLA-I antibodies and had the compatible HLA epitopes.